Fitness and cognition in the elderly: The Austrian Stroke Prevention Study. (2nd February 2016) - Freudenberger, Paul; Petrovic, Katja; Sen, Abhijit; Töglhofer, Anna Maria; Fixa, André; Hofer, Edith; Perl, Sabine; Zweiker, Robert; Seshadri, Sudha; Schmidt, Reinhold; Schmidt, Helena
Abstract : Objective: To investigate whether greater cardiorespiratory fitness is associated with better global and domain-specific cognitive function. Methods: We investigated 877 participants (aged 65 ± 7 years, 55% women) of the Austrian Stroke Prevention Study. For cardiorespiratory fitness, the maximum oxygen consumption (V[Combining Dot Above]O2 max) was calculated based on weight and maximum and resting heart rate on a treadmill test (mL·kg −1 ·min −1 ). A test battery assessing memory (Bäumler's Lern-und Gedächtnistest), executive function (Wisconsin Card Sorting Test, Trail Making Test–Part B, Digit Span Backward, Alters Konzentrationstest, a computerized complex reaction time task) and motor skills (Purdue Pegboard Test) was administered. Summary measures for cognitive domains and for global cognition were calculated. White matter lesions, lacunes, and brain atrophy were assessed using MRI. Results: Higher V[Combining Dot Above]O2 max was associated with better global (B = 0.024; p = 0.000) and domain-specific cognitive function (memory B = 0.026, p = 0.000; executive function B = 0.009, p = 0.003; motor skills B = 0.012, p = 0.018) after adjustment for age, sex, education years, and Ca 2+ channel antagonists or β-blockers. White matter lesions, lacunes, or brain atrophy did not mediate the effect ( p > 0.05 for all mediators). The interactions of V[Combining Dot Above]O2 max with age, overweight, and APOE ε4 on cognition were not statistically significant ( p > 0.05 for all interaction terms) with the exception of a modulating effect of body mass index on V[Combining Dot Above]O2 max in the memory domain. Conclusions: Higher V[Combining Dot Above]O2 max is associated with better global cognitive function and with better performance in the cognitive domains of memory, executive function, and motor skills in the middle-aged and elderly. The association is not mediated by the presence of white matter lesions, lacunes, and brain atrophy.